Justice Without Democracy? Understanding the Future of Energy Through the Inflation Reduction Act - Lara Briggs; Zack Bowersox (Washington University Journal of Law and Policy, 2024)
The Inflation Reduction Act (“IRA”) is, to-date, the US’ largest climate-related policy, and, as such, is influential in determining the trajectory of future policies. Consequently, the IRA has caused a reconceptualization of energy justice (EJ) and energy democracy (ED) from theoretical concepts to guiding ideologies for assessing climate policy and challenging the status quo. This essay argues that the IRA focuses on distributional energy justice outcomes at the expense of procedural energy justice and energy democracy. To solve this issue, this essay asserts that future climate policy must specifically encourage “prosumer” involvement in energy distribution and decision-making, such as community solar projects, to increase the democratic nature of the energy transition process. Ultimately, it cannot be taken as a given that energy justice and democracy automatically lead to the other, as normative assertions have previously claimed; it is up to scholars and policymakers to actively create a democratic and just energy future.
Keywords: EnergyJustice; EnergyDemocracy; ClimatePolicy; InflationReductionAct; CommunitySolar